During and post COVID-19 pandemic: prevention of cross infection at dental practices in country with tropical climate - Rikko Hudyono; Taufan Bramantoro; Benni Benyamin; Irfan Dwiandhono; Pratiwi Soesilowati; Aloysius Pantjanugraha Hudyono; Wahyuning Ratih Irmalia; Nor Azlida Mohd Nor (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2020)
Background: COVID-19 has been regarded as a new pandemic in the world. This disease is highly contagious and can be transmitted easily through droplets and air. This matter is considered as a red flag to all dentists all over the globe. Until today, there is only a few specific guideline in regards to dental practice during and after the pandemic. The protocol only revolves around the limitation of patients’ appointments and using level 3 personal protection equipment. There is no specific mention on the preparation method of the practice room especially in Indonesia. Purpose: This study aims to review literature on infection control in dental settings during COVID-19 pandemic and discuss possible recommendations based on available evidence. Review: The review also discussed the background of COVID-19, transmission, clinical findings, physicochemical properties, and cross infection in dental practice. Despite the usage of personal protective equipment, the rooms need to be set to specific requirement to reduce contamination inside the room. Until today, COVID-19 transmission must be prevented with the best method available. Conclusion: No single protocol may fully guarantee the safety of the patients and dental workers. We suggest to combine the protocol listed above to minimize to self and cross-contamination ’new normal’ practice.